Quidditch through the ages - Rowling, J.K. (New York, NY : Arthur A. Levine Books, an imprint of Scholastic Inc., 2017)
A copy of a book from the library at Hogwarts, the school where Harry Potter and other young wizards receive their training, providing information about history and conduct of Quidditch, a sport played by competing teams on flying brooms.
"Comic Relief"--Back cover.
"In association with WhizzHard Books."
8.2
5-8
5-8
Keywords: Potter, Harry -- (Fictitious character) -- Juvenile fiction; Potter, Harry -- (Fictitious character) -- Fiction; Potter, Harry (Fictional character) -- Fiction; Games -- Juvenile fiction; Games -- Fiction; Sports -- Fiction; Games -- Fiction; Sports -- Fiction; Fantastic fiction